SYNTHESIS OF MENTHOL FROM PULEGOL CATALYZED BY Ni/γ-Al2O3 - Jamaludin Al Anshori; Muchalal Muchalal; Sutarno Sutarno (Indonesian Journal of Chemistry, 2009)
Synthesis of menthol using Ni/γ-Al2O3 15% has been carried out started from pulegol as precursor. Structure elucidation of the products was achieved by GC-FID, GC-MS, FTIR, and 1H-NMR evidences. Isomers identification and their stability were determined by computational simulation. All experimental results were compared to the available literature. Ni/γ-Al2O3 catalyst was prepared by wet impregnation with precursor of Ni(NO3)2, followed by calcinations and reduction respectively. Characterization of the catalyst was performed by XRD and AAS. Synthesis was started by mixing pulegols with catalyst and then swirled it with hydrogen gas. Reaction temperature and duration were varied in order to obtain high yield with good selectivity. The results showed that the optimum condition of Ni/γ-Al2O3 catalytic hydrogenation of pulegol was achieved at 180 °C for 8 hours. The conversion of pulegol to menthol was 89% with stereo selectivity of 71% to (-)-menthol.